1299Association between environmental cadmium exposure and plasma and urinary metabolite profiles in Japanese cohort study. (2nd September 2021) - Ishibashi, Yoshiki; Harada, Sei; Eitaki, Yoko; Iida, Miho; Kurihara, Ayako; Hirata, Aya; Shibuki, Takuma; Okamura, Tomonori; Hirayama, Akiyoshi; Sugimoto, Masahiro; Soga, Tomoyoshi; Tomita, Masaru; et al.
Abstract: Background: The purpose of this study was to identify plasma and urinary metabolites that can be used to better identify the effects of cadmium exposure than N-acetyl-β-D-glucosaminidase (NAG) using capillary electrophoresis - mass spectrometry (CE-MS). Methods: Urinary cadmium (U-Cd) was measured as an indicator of cadmium exposure. Fasting plasma and urine samples were collected from 1, 412 men and 2, 022 women in Tsuruoka Metabolomics Cohort Study. Charged 94 plasma and 123 urinary metabolites were detected and determined. Regression analysis was performed for urinary NAG, plasma, and urinary metabolites as dependent variables and U-Cd in quartiles as an independent variable. Multivariate regression model included age, SBP, smoke, rice intake, BMI, HbA1c, LDLc, alcohol consumption, physical activity, educational history, dietary energy intake, urinary Na/K ratio, and uric acid. Results: The mean U-Cd of the population was 2.65 μg/g creatinine (SD: 1.63). NAG was positively associated with U-Cd, but the association was not significant with lower U-Cd quartiles. In the plasma metabolites, 10 metabolites had significantly negative association with U-Cd in all models and Cd quartiles. Among urinary metabolites, 27 metabolites had significantly positive association with U-Cd. Alanine was negatively associated with U-Cd in urinary metabolites. The trend test also showed significant dose-response trends for 9 plasma and all 28 urinary metabolites (p < 0.05). Conclusions: We found that the levels of Cd exposure, which did not cause an increase in NAG, caused changes in plasma and urinary metabolites. Key messages: This study indicated that metabolomics might be promising and useful as markers of Cd exposure.